Penerapan Firewall Dan Protokol IpSec/L2TP Sebagai Solusi Keamanan Akses Jaringan Publik - Muhammad Ayub; Andry Maulana; Ahmad Fauzi (Computer Science (CO-SCIENCE), 2021)
Firewall is an algorithm that allows filtering activities to determine access restrictions on a komputer  that can use Publik  network access and which komputer s cannot pass through Publik  network access, this is commonly called filtering. As time goes by, the development of today's technology is increasing rapidly. that the sophistication of technology is a major influence in facilitating human life. Based on this, the authors create a Firewall and IpSec/L2TP Protocol as a Security Solution for PT.Neu Indonesia, which aims to prevent attacks on the types of malware found on a site circulating on Publik  networks by filtering it with the use of the firewall itself so that the risk of crime in the cyber world can minimize the occurrence of illegal access that can enter the PT.Neu Indonesia network.